2009
DOI: 10.1007/s12134-008-0083-7
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting migrant nurses to fill the gaps: the contribution of migrant women in the nursing care sector in Greece

Abstract: The study examines the complex and stratified nature of the health care profession in Greece, which is increasingly staffed and thus shaped by female migrants. The research explores how immigrant labour is drawn on to fill the most urgent needs in the lower end of the nursing care sector, how immigrant labour gains access to these jobs, the implications of the recruitment process and the effect of these factors on the local labour market structure. It is shown that a predominantly female migrant cohort provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…There are many nursing agencies: they advertise in newspapers and on websites, which display photographs and offer some background information of the carers. It has also been reported that agencies send representatives into hospitals to distribute cards/flyers with agency contact details for the recruitment of illegal PDNs (Groutsis 2009).…”
Section: Employment Patterns Of Illegal Pdnsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many nursing agencies: they advertise in newspapers and on websites, which display photographs and offer some background information of the carers. It has also been reported that agencies send representatives into hospitals to distribute cards/flyers with agency contact details for the recruitment of illegal PDNs (Groutsis 2009).…”
Section: Employment Patterns Of Illegal Pdnsmentioning
confidence: 99%
“…In addition, when the agencies have helped immigrants – through trafficking and with fraudulent papers – they expect repayment. Blackmail and violence have been reported if repayment is ever defaulted upon (Groutsis 2009).…”
Section: Pay and Working Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, skilled migrants who have obtained their education and training in their home country as opposed to their host country often find themselves at a strategic disadvantage (Groutsis, 2006;Williams, 2007). This is particularly likely to occur when work practices and social norms are markedly different in both countries, causing migrants to participate in migrant networks rather than indigenous networks which creates an 'us' and 'them' division in work and everyday life (Groutsis, 2009;Harvey, 2008b).…”
Section: Integrationmentioning
confidence: 99%
“…In the last two decades there has been a steady growth of research on skilled migrants in multiple regions at different points in time (see Al Ariss and Özbilgin, 2010;Beaverstock, 2002Beaverstock, , 2005Groutsis, 2009;Harvey, 2011aHarvey, , 2011bIredale, 2001;Koser and Salt, 1997;Ley, 2010;Richardson and McKenna, 2003;Saxenian, 2006;Yeoh and Willis, 2005). This research has focused on a range of topics, including but not limited to: immigration, return migration, brain drain, brain waste, brain circulation, government immigration policy, integration, finding work, expatriate and impatriate assignments, social networks and gender inequality.…”
Section: Introductionmentioning
confidence: 99%